Relación entre los esfuerzos de compresión simple y cantidad de flúor en el tejido óseo - Mena Collazos, Luz Angela (Revista Estomatología, 1993)
The relationship between the amount of fluoride in bone and its resistance to simple compression was investigated. 12 samples were analized from the 5th ribofhuman beings taken from fresh corpse with no more than 24 hours after death, in the Legal Medicine Institute of Medellín. The chosen corpses should have complete data concerning: age, sex, place of residence (address) and aclinical history refered by its relatives, and it couldn't present any previous sistemic illness; subsequently a research in their difTerent places of residence was done, to investigate if the water used contained fluoride. The importance of fluoride was determined with the method described by Alhavain 1980, and the resistance to simple compression was determinated throughout the method described by Franke (1976). In the final results no statisticaly significant differences were obtained between the amount of fluoride in the bone sample and its resistance to compression